Prokrastinasi Akademik Siswa SMK: Media Sosial, Efikasi Diri, Konformitas, dan Moderasi Kontrol Diri - Siti Suryani; Mardi; Khansha Sindra Irfani (Qalam : Jurnal Ilmu Kependidikan, 2026)
Task delay among vocational learners runs parallel to the rising intensity of social media use, yet their link remains loosely mapped. This study weighed social media use intensity, self-efficacy, and peer conformity against academic procrastination, and tested self-control as a moderating variable. A quantitative survey reached 152 grade-eleven learners of the Accounting and Financial Institution cluster in three state vocational schools in Central Jakarta, drawn by proportional random sampling. A five-point Likert questionnaire supplied the data, which were processed through Partial Least Square structural equation modelling in SmartPLS. Social media use intensity and peer conformity move in the same direction as delaying behaviour, whereas self-efficacy moves against it; all three are significant. Self-control interaction terms are negative and significant along every path, and the model accounts for 78.2 per cent of the variance. Strengthening self-control therefore deserves to sit at the centre of any intervention.